Multielement (P‐Yb‐Zr‐Ce‐Al‐Ca) fiber for moderate‐power laser application with enhanced photodarkening resistivity. Issue 6 (20th February 2017) - Dhar, Anirban; Das, Shyamal; Reddy, Pinninty Harshavardhan; Siddiki, Salim H.; Dutta, Debjit; Pal, Mrinmay; Kir'yanov, Alexander V.; Paul, Mukul Chandra
Abstract : Multielement (ME) (P‐Yb‐Zr‐Ce‐Al‐Ca) nanophase separated silica‐glass‐based optical fiber is fabricated through a conventional‐modified chemical vapor deposition (MCVD) process, coupled with solution doping technique. The lasing and photodarkening behaviors of this ME fiber have been demonstrated and compared, in terms of its photodarkening (PD) performance at moderate pump powers (tens of Watts), with standard Yb‐doped fiber with phospho‐alumino‐silicate (PAS) glass composition, which clearly reveals that the ME‐Yb doped fiber is a promising candidate for laser applications with enhanced PD resistivity.